Numerical investigation of a MCFC (Molten Carbonate Fuel Cell) system hybridized with a supercritical CO2 Brayton cycle and compared with a bottoming Organic Rankine Cycle. (15th December 2015) - Baronci, Andrea; Messina, Giuseppe; McPhail, Stephen J.; Moreno, Angelo
Abstract: The investigation has the aim to study the integration of a molten carbonate fuel cell and a Brayton cycle, that uses supercritical carbon dioxide (S–CO2 ) as working fluid. The coupling turns out to be feasible achieving 56.25% electrical efficiency at the beginning of cell life, and counteracts the degradation of the MCFC (Molten Carbonate Fuel Cell) over time by converting the extra heat to electricity. The proposed system has been compared with a more conventional system based on the integration of a MCFC system with an ORC (Organic Rankine Cycle) turbine. The boost in electrical efficiency obtained with a Brayton cycle is twice that of a recovery system based on an ORC cycle. Highlights: Integrated model of Molten carbonate fuel cell with supercritical CO2 bottom cycle. MCFC (Molten Carbonate Fuel Cell) black box model validated with real data from a commercial system. Comparison with an Organic Rankine Cycle recovery shows better performance.